Clinical characteristics of hospitalized patients with SARS‐CoV‐2 infection: A single arm meta‐analysis. Issue 6 (11th March 2020) - Sun, Pengfei; Qie, Shuyan; Liu, Zongjian; Ren, Jizhen; Li, Kun; Xi, Jianing
Abstract: Objective: We aim to summarize reliable evidence of evidence‐based medicine for the treatment and prevention of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) by analyzing all the published studies on the clinical characteristics of patients with SARS‐CoV‐2. Methods: PubMed, Cochrane Library, Embase, and other databases were searched. Several studies on the clinical characteristics of SARS‐CoV‐2 infection were collected for meta‐analysis. Results: Ten studies were included in Meta‐analysis, including a total number of 50466 patients with SARS‐CoV‐2 infection. Meta‐analysis shows that, among these patients, the incidence of fever was 0.891 (95% CI: 0.818, 0.945), the incidence of cough was 0.722 (95% CI: 0.657, 0.782), and the incidence of muscle soreness or fatigue was 0.425 (95% CI: 0.213, 0.652). The incidence of acute respiratory distress syndrome (ARDS) was 0.148 (95% CI: 0.046, 0.296), the incidence of abnormal chest computer tomography (CT) was 0.966 (95% CI: 0.921, 0.993), the percentage of severe cases in all infected cases was 0.181 (95% CI: 0.127, 0.243), and the case fatality rate of patients with SARS‐CoV‐2 infection was 0.043 (95% CI: 0.027, 0.061). Conclusion: Fever and cough are the most common symptoms in patients with SARS‐CoV‐2 infection, and most of these patients have abnormal chest CT examination. Several people have muscle soreness or fatigue as well as ARDS. Diarrhea, hemoptysis, headache, sore throat, shock, and other symptoms are rare. The case fatality rate of patients with SARS‐CoV‐2 infection is lower than that of Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS). This meta‐analysis also has limitations, so the conclusions of this Meta‐analysis still need to be verified by more relevant studies with more careful design, more rigorous execution, and larger sample size. Highlights: A total of 10 articles were included in the Meta‐analysis, including 50466 patients with SARS‐CoV‐2 infection, which was by far the first Meta‐analysis with the largest sample size. The quality of the literature included in this study is high, the analysis performed is rigorous, and the conclusions drawn by this study are highly credible.